Review paperSpecificity of rheumatic diseases in occupational medicine practice - Bugajska, Joanna; Jędryka-Góral, Anna (Reumatologia/Rheumatology, 2006)
The aim of the article is to present the issue of rheumatic diseases which could appear in the working environment and to indicate the capacity of ergonomics to protect against those problems. Practical medical and organizational aspects as well as legal background regarding those issues are presented.